1992
DOI: 10.1079/bjn19920071
|View full text |Cite
|
Sign up to set email alerts
|

Splanchnic fluxes of amino acids after duodenal infusion of carbohydrate solutions containing free amino acids or oligopeptides in the non-anaesthetized pig

Abstract: _~~_ _ _Seven non-anaesthetized pigs (mean body-weight 64.6 kg) were used to study the intestinal absorption and hepatic metabolism of glucose and amino acids (AA) using carbohydrate solutions (maltose dextrin; 440 g/2 I), containing 110 g of either an enzymic milk-protein hydrolysate (PEP) with a large percentage of small peptides (about 50% with less than five AA residues) and very few free AA (8%) or a mixture of free AA (AAL) with an identical pattern, infused intraduodenally. Each pig was previously fitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 66 publications
8
70
1
1
Order By: Relevance
“…Thus, to study the total absorption of nutrients originating from the enzymatic digestion, the establishment of intestinal balances for a given meal would require blood samplings for 18 h h during the postprandial period. However, according to the variation in the postprandial concentrations of these nutrients the porto-arterial differences generally became low or nil after hour 12 The portal flow rate expressed relative to the animal weight (mL/kg/min) was slightly lower than in previous studies [25,33]. This difference can be explained by the fact that, in the present experiment, the animals were heavier than in the previous ones.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Thus, to study the total absorption of nutrients originating from the enzymatic digestion, the establishment of intestinal balances for a given meal would require blood samplings for 18 h h during the postprandial period. However, according to the variation in the postprandial concentrations of these nutrients the porto-arterial differences generally became low or nil after hour 12 The portal flow rate expressed relative to the animal weight (mL/kg/min) was slightly lower than in previous studies [25,33]. This difference can be explained by the fact that, in the present experiment, the animals were heavier than in the previous ones.…”
Section: Discussioncontrasting
confidence: 54%
“…The main limitation of this method is related to the metabolism in the epithelial cells which can take up a part of the nutrients released in the intestinal lumen (glucose and amino acids: Rerat et al [33]), but also metabolites produced by microbial fermentation [18]. Addi [23].…”
Section: Discussionmentioning
confidence: 99%
“…14 C meal absorption rate was calculated as: "portal absorption of 14 C / 14 C content in the meal". Blood flow per min and per kg body weight could be estimated thanks many references using growing pigs (Rérat et al, 1987;Simoes Nunes et al, 1989;Rérat et al, 1991;Rérat et al, 1992;Guillot et al, 1993;Guillot et al, 1994;Rérat et al, 1996;Santamaria et al, 1997;Lang et al, 1999;Le Floc'h et al, 1999;Vaugelade et al, 2000).…”
Section: Portal Absorption Calculationsmentioning
confidence: 99%
“…In the case of lysine, the increase in liver uptake helps to limit lysine accumulation in the systemic plasma by favoring lysine catabolism in the liver. In pigs, threonine seem to be less efficiently extracted into the liver than the other essential AA [20]. In a previous study using labelled tracer, we have shown that threonine entry in the liver was low and fairly constant for low and adequat dietary supplies, which corresponds to the experimental situations of experiment 1, but increased sharply with excess supply [12].…”
Section: Effect Of Threonine and Lysine Dietary Balance On Their Utilmentioning
confidence: 99%